Assessment of standalone solar PV-Battery system for electricity generation and utilization of excess power for water pumping. (December 2019) - Bhayo, Bilawal A.; Al-Kayiem, Hussain H.; Gilani, Syed I.
Graphical abstract: An assessment methodology for coupled PV-Battery system with the feature of utilizing the excess power for another application is developed and demonstrated. Water pumping is considered as the secondary application for excess power utilization. Energy management would be carried out for the maximum utilization of PV power and minimum utilization of battery storage. Highlights: Excess power generated from PV-Battery system is unavoidable. Excess power from PV-Battery system is assessed for water pumping. Sizing of standalone PV-Battery system with 100% power reliability is determined. Economic feasibility analysis of standalone PV-Battery system is carried out. Abstract: This study presents a developed assessment methodology for Photovoltaic-Battery power system featured with utilization of the dumbed power for secondary applications such as water pumping. Primary target is to meet the demand of 3.2 kWh/day for rural housing unit. The PV-Battery system size is determined by varying the number of PV's and Battery capacity. At each configuration, having the Loss of Power Supply Probability of 0, the Levelized Cost of Energy is determined. It has been revealed that the number of PV panels are depending on a day with lowest solar irradiations. However, the required battery storage is contingent on the maximum number of hours the battery is required to supply power to the load. In the present study, the battery can supply power for maximum of 16 h such as starting from 4:00 PM to 7:00 AM next day. The selected size of PV-Battery system to meet the load demand of 3.2 kWh/day and utilize the excess power for water pumping consists of 2.44 kWp of PV's and 3.55 kWh of installed battery capacity. The selected power system generates an average 9.807 kWh/day and provides the water pumping of 363 m 3 /day. The power yield in peak hours and Levelized Cost of Energy are 58.6% and 0.3750 /kWh, respectively. It is reviled that the excess power is unavoidable, and it is recommended to be utilized for water pumping. If the water is pumped to elevated storage, it may be used for extra hydro power generation by hybrid PV-Battery-Hydro power.